Mirabegron relaxes urethral smooth muscle by a dual mechanism involving β3-adrenoceptor activation and α1-adrenoceptor blockade - Alexandre, E. C.; Kiguti, L. R. [UNESP]; Calmasini, F. B.; Silva, F. H.; Silva, K. P. da [UNESP]; Ferreira, R.; Ribeiro, C. A. [UNESP]; Mónica, F. Z.; Pupo, A. S. [UNESP]; Antunes, E. (Wiley Online Library, 2015)
Mirabegron is the first β3-adrenoceptor (AR) agonist approved for treatment of overactive bladder syndrome (OAB). This study aimed to investigate the effects of β3-adrenoceptor (AR) agonist mirabegron in mouse urethra. The possibility that mirabegron exerts α1-AR antagonism was also tested in rat smooth muscle preparations presenting α1A- (vas deferens and prostate), α1D- (aorta) and α1B-AR (spleen). Functional assays were carried out in mouse and rat isolated tissues. Competition assays for the specific binding of [(3) H]Prazosin to membrane preparations of HEK 293 cells expressing each of the human α1-ARs, as well as β-AR mRNA expression and cyclic AMP measurements in mouse urethra were performed. Mirabegron produced concentration-dependent urethral relaxations that were right shifted by the selective β3-AR antagonist L 748,337, but unaffected by β1- and β2-AR antagonists (atenolol and ICI 118,551, respectively). Mirabegron-induced relaxations were enhanced by the phosphodiesterase-4 inhibitor rolipram, and this agonist stimulated cAMP synthesis. Mirabegron also produced rightward shifts in urethral contractions induced by the α1-AR agonist phenylephrine. Schild regression analysis revealed that mirabegron behaves as a competitive antagonist of α1-AR in urethra, vas deferens and prostate (α1A-AR, pA2  ≅ 5.6) and aorta (α1D-AR, pA2  ≅ 5.4), but not in spleen (α1B-AR). The affinities estimated for mirabegron in functional assays were consistent with those estimated in radioligand binding with human recombinant α1A- and α1D-ARs (pKi ≅ 6.0). The effects of mirabegron in urethral smooth muscle are the result of β3-AR agonism together with α1A / α1D-AR antagonism.
Keywords: Cyclic amp; ISoprenaline; Lower urinary tract symptoms; Mirabegron; Overactive bladder syndrome; Rolipram; Α1-adrenoceptors; Β3-adrenoceptor